Economic Crisis and the Fragility of Comparative Advantage in European Agriculture - Stefan Bojnec; Imre Ferto (German Journal of Agricultural Economics (GJAE), 2018)
The paper investigates the impact of the economic crisis on the duration of comparative advantage of agri-food products in European Union member states during the period 2000-2014 using normalised revealed comparative advantage indices. Specifically, we examine how the economic crisis affected comparative advantage indices at 1) the start of a period of comparative advantage, 2) during a period of comparative advantage, and 3) how quickly comparative advantage grew within a defined period. Duration and regression analyses are applied to examine the fragility of comparative advantage indices using alternative model specifications and estimation procedures. Estimations suggest that the comparative advantage for most agri-food products is short lived. Economic crisis reduces the duration and growth of comparative advantage, while spell duration, lag in comparative advantage and product differentiation reduce the probability of failure of duration of comparative advantage. Economic crisis and the duration of a period after-crisis reduce, and a period after-crisis and crisis-duration increase the growth of comparative advantage. These results are relevant for EU agri-food exporting countries, as the fragility of comparative advantage is found to be driven by both endogenous factors and the exogenous macro-economic-related shock of economic crisis. Exit from economic crisis and product differentiation have strengthened the comparative advantage of EU-28 member states in terms of differentiated agri-food product varieties for final consumption.
Keywords: 330